2008
DOI: 10.1098/rspb.2008.0647
|View full text |Cite
|
Sign up to set email alerts
|

Kin recognition in zebrafish: a 24-hour window for olfactory imprinting

Abstract: Distinguishing kin from non-kin profoundly impacts the evolution of social behaviour. Individuals able to assess the genetic relatedness of conspecifics can preferentially allocate resources towards related individuals and avoid inbreeding. We have addressed the question of how animals acquire the ability to recognize kin by studying the development of olfactory kin preference in zebrafish (Danio rerio). Previously, we showed that zebrafish use an olfactory template to recognize even unfamiliar kin through phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 34 publications
(42 reference statements)
2
113
0
Order By: Relevance
“…In fish olfaction also plays a major role in intra-specific communication (Stacey and Sorensen, 2002), including social recognition (Gerlach et al, 2008). Although an AVT neuronal population has never been described in the olfactory bulbs of teleosts, V1a receptors have been identified in this area (Kline et al, 2011), which together with the high AVT peptide levels reported here, suggest a role for AVT in the processing of olfactory stimuli in fish.…”
Section: Discussionmentioning
confidence: 48%
“…In fish olfaction also plays a major role in intra-specific communication (Stacey and Sorensen, 2002), including social recognition (Gerlach et al, 2008). Although an AVT neuronal population has never been described in the olfactory bulbs of teleosts, V1a receptors have been identified in this area (Kline et al, 2011), which together with the high AVT peptide levels reported here, suggest a role for AVT in the processing of olfactory stimuli in fish.…”
Section: Discussionmentioning
confidence: 48%
“…Chemically-mediated attraction behaviors are diverse and include appetitive olfactory behavior (elicited by L-alanine, food extract and others), chemically mediated kin recognition and sexual aggregating behavior (elicited by sex pheromones). [73][74][75]96,97 Usually characterized by higher speed as fish follow the increasing concentrations of chemoattractants and by slower speed when fish locate the signal source. 1.31.…”
Section: Chemotaxis (Chemoattraction)mentioning
confidence: 99%
“…Namely, zebrafish can learn (Darland and Dowling, 2001;Sison and Gerlai, 2010) and are amenable to neurodevelopmental and neurogenetic analysis and manipulation (Asakawa et al, 2008;Baier and Scott, 2009). Even in an early stage of development zebrafish larvae possess a wide spectrum of innate and experience-dependent behaviors (Burgess and Granato, 2007;Gerlach et al, 2008). Importantly, their relatively small size, manageable number of neurons, and optical accessibility make them attractive for studying the neural mechanisms of behavior (Friedrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%